APPLICATION OF A MULTILEVEL FIREFLY ALGORITHM ON A LARGE VARIABLE NUMBER LOGISTIC PROBLEM - Kota, László; Jármai, Károly (Advanced Logistic Systems - Theory and Practice, 2021)
During our research and industrial projects, we often meet difficult optimization problems, a lot of variables, a lot of constraints, nonlinear and mostly discrete problems, where the running time can be calculated sometimes in weeks with the usual optimization methods on an average computer. In the most cases in the logistic industry the strongest constraint is the time. The optimizations are running on a usual office configuration and the company accepts the suboptimal solution what the optimization method gives in the appropriate time limit. In this article we will investigate a multilevel method on supply chain problem, to increase the effectivity, improve the solution in a strict time condition.